Awareness, Perception, and Knowledge of Amblyopia among the Community in Madinah, Saudi Arabia: A 2020 Study - Alahmadi, Ghaida M.; Aziz, Ghaida A. (Journal of King Abdulaziz University: Medical Sciences, 2023)
An analytical cross-sectional study was carried out, and was conducted to assess the knowledge, awareness, and perception about amblyopia among the community in Madinah, Saudi Arabia, during February 2020. A total of 633 who satisfied the inclusion criteria were acquired. A chain sampling technique was carried out. Structured valid questionnaire (in Arabic) were distributed to the respondents using (WhatsApp) application. The collected data were analyzed by appropriate statistical tests. Results showed that of the 633 participants, only onethird (33.8%, n = 214) mentioned that they are knowledgeable about this condition. Of them, one-fourth (27.6%) had a correct knowledge about the definition of amblyopia with (29.8%) who identified refractive errors, strabismus and cataract as etiologies of amblyopia and (84.1%) mentioned early treatment as more effective. Results showed that respondents with higher education level (64.3%), who were in health-related field (44.8%) and parents who had amblyopic children (70.4%) were found to have more significant awareness (p < 0.05). In conclusion, low awareness on amblyopia was found to be common topic among previous and current researches in relation with the disease. This gap in awareness can be minimized by directing more efforts to provide a greater reach on disease information dissemination. Public campaigns are deemed vital in promoting more information about the disease.